A Review of English for Vocational High School in Curriculum Merdeka - Wafa’ Qaulan Syahida; Siminto Siminto (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This research aims to determine the effect of the curriculum Merdeka on Vocation High School students. This study uses a descriptive qualitative approach with library research methods. The data collection technique is by collecting several references, such as books, articles, and other related sources. Then the data analysis technique used in this research is content analysis, with the stages of presenting data, data reduction, data verification, and concluding. In this study uses descriptive qualitative research. The results of the study show that there is an influence of the curriculum Merdeka on Vocation High School students and the impact is that students can work well in their respective fields. Meanwhile, the teacher participates in the process because the way the teacher teaches by implementing the independent curriculum affects students in learning.